O lugar do currículo como objeto de estudo na formação inicial em educação física da Universidade Federal do Pará – Campus Belém - SANTOS, Carlos Afonso Ferreira dos (2020)
This monographic work intends to investigate the curriculum and its place in the initial teacher education of the undergraduate course in Physical Education of the Federal University of Pará (UFPA), Belém Campus. Therefore, the purpose of this study is to identify which theoretical perspectives and potentialities on curriculum study are present in the academic course of the Physical Education course of this institution, based on the assumption that it presents a plural character of meaning and several thematic approaches related to educational actions in the school and, properly, to the pedagogical intervention with the Physical Education. The methodological process included documentary analysis of the Pedagogical Political Project of the Faculty of Physical Education of the UFPA Belém, with emphasis on the course syllabus, aiming to diagnose in thematic curricular components associated with the curricular discussion in Physical Education. The results point to an implicit presence of discussions that navigate between the thematic approaches of the curriculum, similar to other own knowledge of the pedagogical field and Physical Education, as well as visualized potentialities in components that have a strong tendency to deal with the study of the curriculum and its subjects. To that extent, it is concluded that the training in Physical Education of UFPA Belém has to visualize in the curriculum a necessary object of study for the purposes of the field in the school area, considering the intrinsic relation between both fields. In addition, it is analyzed the viable intention of this same formation not to focus exclusively objectivity to the study of the curriculum, once of the announced necessity of the academic treatment to the own knowledge of the field of Physical Education. On the other hand, the explicit study of this object, in an interdisciplinary and transversal way, is also essential to reinforce the curricular perspective in the educational dynamics with Physical Education in the school environment.